Revisiting the effects of government size and labour market institutions on macroeconomic volatility: the case of the eurozone - Bajo-Rubio, Oscar; Berke, Burcu (Economics and Business Letters, 2023)
We revisit the role of government size and labour market institutions on macroeconomic volatility, for the case of the eurozone since the adoption of the euro, which can provide a more homogeneous setting to test for macroeconomic volatility. The behaviour of the volatility of inflation looked rather different from that of GDP. Neither government size nor labour market institutions seemed to affect the volatility of GDP, except when demographic factors were included into the estimated equation; whereas lower volatility of inflation was related to a lower share of non-prime age workers and lower wage volatility.